The Efficacy of Endoscopic Submucosal Dissection of Type I Gastric Carcinoid Tumors Compared with Conventional Endoscopic Mucosal Resection - Hyung Hun Kim; Gwang Ha Kim; Ji Hyun Kim; Myung-Gyu Choi; Geun Am Song; Sung Eun Kim (Gastroenterology Research and Practice)
Background and Aims. Conventional endoscopic submucosal resection (EMR) of carcinoid tumors often involves the resection margin, which necessitates further intervention. Endoscopic submucosal dissection (ESD) is widely accepted for removing carcinoid tumors. We aimed to evaluate the clinical usefulness of ESD with that of EMR for resection of type I gastric carcinoid tumors. Patients and Methods. The study enrolled 62 patients (37 males, 25 females; median age, 50 years; range, 40–68 years) who were treated with EMR or ESD at three hospitals; the study group had 87 type I gastric carcinoid tumors with an estimated size of ≤10 mm. The complete resection rate and the complications associated with these two procedures were analyzed. Results. The overall ESD complete resection rate was higher than that of the EMR rate (94.9% versus 83.3%, P value = 0.174). A statistically lower vertical margin involvement rate was achieved when ESD was performed compared to when EMR was performed (2.6% versus 16.7%, P value = 0.038). The complication rate was not significantly different between the two groups. Conclusions. ESD showed a higher complete resection rate, particularly for the vertical margin, with a similar complication rate. We mildly recommend ESD rather than EMR for removing type I gastric carcinoid tumors.